DESKRIPSI KESALAHAN PEMBUATAN RENCANA PELAKSANAAN PEMBELAJARAN DITINJAU DARI TINGKAT RASA PERCAYA DIRI MAHASISWA - Anggun Badu Kusuma; Gunawan Gunawan (INSPIRAMATIKA, 2017)
This study aims to describe the results of making the implementation plan of learning conducted by students in terms of students' confidence level in the basic course of mathematics learning process students in the third semester of class B Mathematics Education Study Program, University of Muhammadiyah Purwokerto academic year 2016/2017. This research is included in qualitative descriptive research. Data obtained from questionnaires and documentation. Questionnaire data is used to determine students' confidence level. From the results of the questionnaire is then the basis of student grouping. Data data that is RPP result of student work and photo activity. From the student's RPP is then analyzed to produce errors made by students in making RPP. The result of the research shows that (1) the respondents who have low confidence in the form of the content and completeness of the elements of RPP, (2) the confident respondents are lacking in the form of the content of each RPP, and (3) the respondents who have a high confidence can be able to compile and the content of all elements of the appropriate RPP.